Recommendations on diagnostic tools for Batrachochytrium salamandrivorans. Issue 2 (17th January 2018) - Thomas, V.; Blooi, M.; Van Rooij, P.; Van Praet, S.; Verbrugghe, E.; Grasselli, E.; Lukac, M.; Smith, S.; Pasmans, F.; Martel, A.
Summary: Batrachochytrium salamandrivorans ( Bsal ) poses a major threat to amphibian, and more specifically caudata, diversity. Bsal is currently spreading through Europe, and mitigation measures aimed at stopping its spread and preventing its introduction into naïve environments are urgently needed. Screening for presence of Bsal and diagnosis of Bsal ‐induced disease in amphibians are essential core components of effective mitigation plans. Therefore, the aim of this study was to present an overview of all Bsal diagnostic tools together with their limitations and to suggest guidelines to allow uniform interpretation. Here, we investigate the use of different diagnostic tools in post‐mortem detection of Bsal and whether competition between Bd and Bsal occurs in the species‐specific Bd and Bsal duplex real‐time PCR. We also investigate the diagnostic sensitivity, diagnostic specificity and reproducibility of the Bsal real‐time PCR and show the use of immunohistochemistry in diagnosis of Bsal ‐induced chytridiomycosis in amphibian samples stored in formaldehyde. Additionally, we have drawn up guidelines for the use and interpretation of the different diagnostic tools for Bsal currently available, to facilitate standardization of execution and interpretation.